Customer Preferences in Choosing Ijarah Contracts at Islamic Banks - Husnul Khatimah; Marliyah Marliyah; Juliana Nasution (Academia Open, 2025)
General Background: Islamic financing contracts, such as the Ijarah Agreement, are vital instruments in Sharia-based banking. Specific Background: Despite their growing adoption, limited research has empirically explored the determinants of their use among Bank Syariah Indonesia (BSI) clients. Knowledge Gap: There is a lack of understanding regarding which factors significantly drive customer decisions toward Ijarah products. Aims: This study aims to identify and assess the key factors influencing the adoption of Ijarah Agreements among clients of Bank BSI Lubuk Pakam. Results: Using a quantitative descriptive approach with purposive sampling of 40 respondents, the study employed SPSS 22 for statistical analysis, including normality, regression, and significance testing. The results show that product quality and margins significantly affect customer decisions, whereas service quality and financing methods have negligible impact. The adjusted R² value of 0.629 indicates that 62.9% of decision variance is explained by the tested variables. Novelty: This study offers new empirical insights into how specific product attributes and profitability shape customer behavior in Ijarah financing. Implications: The findings underscore the need for Sharia banks to prioritize product excellence and competitive margins to enhance Ijarah adoption. Highlights: Highlights the dominance of product quality and margin in customer choices. Uses empirical analysis through SPSS on BSI clients. Reveals service quality has limited impact on Ijarah adoption. Keywords: Ijarah Contracts, Customer Decision, Islamic Banking, Product Quality, Profit Margin